The Role of Blood Platelets in Experimental Metastases - Hilgard, P. (Nature Publishing Group, 1973)
After the intravenous injection of Walker 256 tumour cells into rats the platelet count decreased rapidly and remained low during the following period of observation. The platelet decrease was closely related to the number of cells injected. Intra-arterial tumour cell injections required a considerably higher tumour cell count to produce a comparable thrombocytopenia. Non-viable tumour cells and tumour cell fragments induced a similar decrease of circulating platelets. Neither viable tumour cells nor tumour cell fragments aggregated rat platelets in vitro. The presence of fibrin monomers in tumour cell injected animals suggested intravascular fibrin deposition; the plasma fibrinogen level, however, did not decrease significantly. Isotope studies using (51)Cr labelled platelets revealed a rapid disappearance of the platelets from the circulation and their trapping in the lung—the primary site of tumour cell lodgement. Dipyridamole and ancrod pretreatment did not influence the decrease of platelets and their accumulation in the lung after tumour cell injection. In contrast, heparin completely prevented the thrombocytopenia and the platelet trapping in the lung. From the present experiments it is concluded that embolic tumour cells lead to early endothelial damage, resulting in local thrombin formation with subsequent irreversible platelet aggregation.